Pengembangan Media Pembelajaran Menggunakan Adobe Flash CS6 Pada Mata Pelajaran Dasar-Dasar Program Keahlian Kelas X di SMK Muhammadiyah 1 Wonosobo - Salasta Nastika Maulidya; Priyanto; Eko Marpanaji (Journal of Information Technology and Education (JITED), 2023)
This study aims to develop and test the feasibility of learning media in the basics of skill programs for class X SMK Muhammadiyah 1 Wonosobo using Adobe Flash CS6. The lack of optimal use of smartphones and student motivation in learning is a factor in students' difficulties in learning advanced material. The research method uses R&D with the ADDIE model. The research starts from (1) analyzing problems, needs, and devices (2) designing flowcharts, storyboards, and materials (3) making media using Adobe Flash CS6 and testing by material experts and media experts (4) implementation with trials to students and (5) evaluation. Learning media testing from material experts scored 75% (feasible) and media experts gave a score of 81% (very feasible). Testing by students scored 84% (very feasible). Based on the assessment score, it shows that the learning media developed is feasible to use to support the student learning process. In addition, the existence of this learning media proves that this media is able to increase student motivation in learning.